(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Non-banking financialcompanies (NBFCs) form an integral part of the Indian financial system. Thehistory of the NBFC Industry in Indiais a story of under-regulation followed by over-regulation. Policy makers haveswung from one extreme position to another in their attempt to set controls andthen restrain them so that they do not curb the growth of the industry. Most ofNBFCs’ are operating with high risk of lending and more often NBFCs’ lendcredit to Small and Medium size enterprises, which are categorized as high riskclass of Assets. This paper aim is to Assess Risk for NBFCs’ based on bothqualitative and quantitative aspects of the client.